The most critical failures by discontinuities adjustment factor - Ismail Abd Rahim (Faculty of Science and Natural Resources, 2020)
Some of the rock cut slopes shows difference mode of failure from their appearance as well as more than one failure in Markland test. Then to select the most potential failure for stability analysis will become a difficult task. The selection will be depending on the experience of a geologist or geotechnical engineer. But, this kind of selection is not always acceptable by others geologist or geotechnical engineer because most of them believe in numbers. To solve this problem, the discontinuity adjustment factors (F) approach in Slope Mass Rating (SMR) was used and found working well in determining the most potential failure for slope stability analysis. This F approach's result is also supported by limit equilibrium analysis (FOS value).